Effect of fly ash as partial cement replacement on workability and strength on water cured lightweight concrete - Nur Fazliana, Muhamad Razali (2018)
Fly ash generated from coal power plant is disposed as environmental polluting waste. The use of cement in construction cause the greenhouse gas emission that produces from the cement production. It is also not eco-friendly environment and costly for construction in this era. In addition, palm oil boiler stone is a waste by-product of palm oil milling that causes the increasing of dumping area. In this study, this research investigates the effect of fly ash as partial cement replacement on workability, compressive strength and flexural on water cured lightweight concrete. Five types of mixes with various percentage of fly ash as partial cement replacement content were used. The first mixes are 0% of fly ash act as control specimen and the others contains 10%, 20%, 30% and 40% of fly ash content. The compressive strength and flexural strength were determined at 7, 14 and 28 days. Findings show that strength is increasing as a percentage of fly ash used increase. The highest compressive strength is 10% of fly ash used in concrete. Similar trend were observed in flexural strength result. Fly ash being a pozzolanic material causes pozzolanic reaction in concrete mix which increases amount of total C-S-H gel. As a result, the concrete become denser and stronger.